2022
DOI: 10.1002/pul2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of risk assessment tools in management of PAH: A PAH provider survey

Abstract: Pulmonary arterial hypertension (PAH) is a chronically progressive fatal disease. A goal-oriented approach to achieve low risk status has been associated with improved survival. A variety of risk stratification tools are available, but use is low. We conducted a survey to assess potential reasons for under-utilization. We conducted a survey-based study of global PAH disease specialists with a goal of assessing risk assessment utilization and identifying modifiable barriers to use. The survey was designed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In February 2020 to April 2020 primary care telemedicine visits moved from <1% to nearly 43%, and now between 60% and 90% of physicians are using telemedicine services to some extent. The ACCP PVD Network steering committee found that 93% of patient care was affected and telemedicine use increased from 15% prepandemic to 84% during the early pandemic 46 …”
Section: Telemedicine Tools: What Are They and How To Best Utilize Th...mentioning
confidence: 99%
“…In February 2020 to April 2020 primary care telemedicine visits moved from <1% to nearly 43%, and now between 60% and 90% of physicians are using telemedicine services to some extent. The ACCP PVD Network steering committee found that 93% of patient care was affected and telemedicine use increased from 15% prepandemic to 84% during the early pandemic 46 …”
Section: Telemedicine Tools: What Are They and How To Best Utilize Th...mentioning
confidence: 99%
“…Risk assessment should be used more regularly as 59-63% utilization among clinicians is far from sufficient. [1][2][3]10 However, risk assessment should not replace clinical gestalt, as the former only fulfils an objective complement to clinical assessment. Given these findings, it is all the more important to implement the 2022 ESC/ERS PH guidelines through integrating risk assessment, irrespective of preferred validated calculation model, into clinical practice to guide treatment in PAH.…”
Section: Dear Editormentioning
confidence: 99%
“…A study by Wilson et al 1 found that nonphysicians compared with physicians had two major issues accounting for the underutilization of risk assessment tools, including lack of education and training (20% vs. 4%), and lack of clarity on the best tool to use (30% vs. 18%). 1 A study by Sahay et al 3 found that risk assessment was used among 63% of clinicians and the most commonly identified barriers of underutilization were time constraints and lack of integration into electronic medical records. Additionally, a study by Simons et al 10 found a 55% discordance between clinical gestalt and calculated risk score, as well as that 80% of patients clinically judged as low-risk were assigned to higher risk categories based on their calculated risk.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…While one survey found that the majority of physicians made palliative care referral at least once in the past 12 months found a much higher rate of utilization (91%), 16 fewer physicians (7%) prompted goals of care and palliative care discussion with their patients. 17 A recently published study by Anand et al provided an in-depth, longitudinal view of specialist palliative care service utilization in patients with PAH. 11 The authors utilized the National Inpatient Sample-a nationwide database of all inpatient admissions for 20% stratified sample of all hospitalizations-from 2001 to 2017 to determine the rate of utilization of palliative care services overall, temporal trends, predictors of use, length of stays, cost, in-hospital mortality, disposition, and use of do-not-resuscitate (DNR) status.…”
Section: Current Guidelinesmentioning
confidence: 99%